REVIEW ARTICLE - WNT/Β-CATENIN SIGNALING IN STEM CELLS: POTENCY FOR REGENERATIVE MEDICINE - Dewi Kurniawati (Farmaka, 2020)
The ability of Wnt ligands to initiate signaling cascades that result in cytoplasmic stabilization, β-catenin underlies their ability to regulate progenitor cell differentiation. In this review, we will summarize current knowledge about the mechanisms underlying Wnt/β-catenin signaling and how pathways regulate the differentiation of normal stem cells in the human body and the role of Wnt/β-catenin signaling in the paracrine effect. It is desirable to have a picture regarding the role of Wnt/β-catenin in Regenerative Medicine.